Symmetric vs. asymmetric punishment regimes for bribery - Christoph Engel; Sebastian J. Goerg; Gaoneng Yu (Max Planck Institute for Research on Collective Goods, 2012)
In major legal orders such as UK, the U.S., Germany, and France, bribers and recipients face equally severe criminal sanctions. In contrast, countries like China, Russia, and Japan treat the briber more mildly. Given these differences between symmetric and asymmetric punishment regimes for bribery, one may wonder which punishment strategy is more effective in curbing corruption. For this purpose, we designed and ran a lab experiment in Bonn (Germany) and Shanghai (China) with exactly the same design. The results show that, in both countries, with symmetric punishment recipients are less likely to grant the socially undesirable favor, while bribers are more likely to report to the authorities with asymmetric punishment. In addition, when punishment was asymmetric, corrupt offers were significantly more likely in Shanghai, but not in Bonn. Our results suggest a tradeoff between deterrence and law enforcement. In a forward-looking perspective, lawmakers must decide which aim carries more weight.
Keywords: D02; K42; C91; D03; K14; D73; 330; Asymmetry; Punishment; Bribery; Effectiveness; Legislation; Korruption; Korruptionsbekämpfung; Strafe; Rechtsdurchsetzung; Test; Deutschland; China